Characterization of genes required for both Rpg1 and rpg4-mediated wheat stem rust resistance in barley - Shyam Solanki; Jonathan Richards; Gazala Ameen; Xue Wang; Atiya Khan; Harris Ali; Alex Stangel; Prabin Tamang; Thomas Gross; Patrick Gross; Thomas G. Fetch; Robert S. Brueggeman (BMC Genomics, 2019)
Abstract Background Puccinia graminis f. sp. tritici (Pgt) race TTKSK and its lineage pose a threat to barley production world-wide justifying the extensive efforts to identify, clone, and characterize the rpg4-mediated resistance locus (RMRL), the only effective resistance to virulent Pgt races in the TTKSK lineage. The RMRL contains two nucleotide-binding domain and leucine-rich repeat (NLR) resistance genes, Rpg5 and HvRga1, which are required for resistance. The two NLRs have head-to-head genome architecture with one NLR, Rpg5, containing an integrated C-terminal protein kinase domain, characteristic of an “integrated sensory domain” resistance mechanism. Fast neutron mutagenesis of line Q21861 was utilized in a forward genetics approach to identify genetic components that function in the RMRL or Rpg1 resistance mechanisms, as Q21861 contains both genes. A mutant was identified that compromises both RMRL and Rpg1-mediated resistances and had stunted seedling roots, designated required for P. graminis resistance 9 (rpr9). Results The rpr9 mutant generated in the Q21861 background was crossed with the Swiss landrace Hv584, which carries RMRL but contains polymorphism across the genome compared to Q21861. To map Rpr9, a Hv584 x rpr9 F6:7 recombinant inbred line (RIL) population was developed. The RIL population was phenotyped with Pgt race QCCJB. The Hv584 x rpr9 RIL population was genotyped with the 9 k Illumina Infinium iSelect marker panel, producing 2701 polymorphic markers. A robust genetic map consisting of 563 noncosegregating markers was generated and used to map Rpr9 to an ~ 3.4 cM region on barley chromosome 3H. The NimbleGen barley exome capture array was utilized to capture rpr9 and wild type Q21861 exons, followed by Illumina sequencing. Comparative analysis, resulting in the identification of a 1.05 Mbp deletion at the chromosome 3H rpr9 locus. The identified deletion contains ten high confidence annotated genes with the best rpr9 candidates encoding a SKP1-like 9 protein and a F-box family protein. Conclusion Genetic mapping and exome capture rapidly identified candidate gene/s that function in RMRL and Rpg1 mediated resistance pathway/s. One or more of the identified candidate rpr9 genes are essential in the only two known effective stem rust resistance mechanisms, present in domesticated barley.